Empowering Healthy & Quality Human Resources Covid-19 Response - Yulia Widhianti; Alfian Ady Saputra; Riyan Ariyansah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
The task of lecturers is to carry out the Tri Dharma of Higher Education, therefore, to provide insight, useful and sustainable, one of which is Community Service, this activity can add insight and knowledge to the community so that students have views on the direction and goals of technological development and are able to foster creativity so that they can understand the problems that occur in the community,  Community Service activities are carried out with stages carried out, namely socialization, program preparation and program implementation. There are some people who lack awareness of the importance of healthy human resources & quality of covid-19 response and the new normal transition period. The importance of socialization about healthy & quality human resources, covid-19 response, and the new normal transition period.  After socializing and educating about the empowerment of healthy & quality human resources in response to covid-19 and the new normal transition period, the community began to understand and understand the importance of empowering healthy & quality human resources so that later they could minimize the impact of poor human resources in the community. and The community is able to overcome the COVID-19 response and the new normal transition period.